1975
DOI: 10.1002/cber.19751081024
|View full text |Cite
|
Sign up to set email alerts
|

Darstellung und Reaktionen von trans‐Cyano(pseudo)halogeno‐bis(triphenylphosphin)platin(II)‐Komplexen

Abstract: Die oxidative Addition von Halogencyan an Pt(PPh3k liefert die gemischten trans-Cyanohalogeno-Komplexe (Ph,P),Pt(X)CN la -c. In diesen kann Halogenid aufgrund des trans-Effekts der Cyanogruppe leicht durch andere anionische Liganden ausgetauscht werden. Die Aid-und Fulminatliganden in ld und g sind besonders reaktiv und lassen sich unter milden Bedingungen in die Iso(thio)cyanato-Gruppe umwandeln. Der durch Cycloaddition von Acetonitril an die Azidgruppe von 1 d gebildete Komplex 4b enthalt N'und N2-gebundene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…Evidence obtained to date indicated that both the two isomers [corresponding to coordination at N(1) and at N(2)] were formed simultaneously [26][27][28]44], or else only the N(2) bound isomer was produced exclusively [27,26,45,46]. In contrast to the result published earlier by our group [13], we here obtain only the N(2) bound isomers for both alkoxy substituted acetylenes.…”
Section: Reaction Of Ruthenium Azido Complexes With Dmd or Dedcontrasting
confidence: 83%
“…Evidence obtained to date indicated that both the two isomers [corresponding to coordination at N(1) and at N(2)] were formed simultaneously [26][27][28]44], or else only the N(2) bound isomer was produced exclusively [27,26,45,46]. In contrast to the result published earlier by our group [13], we here obtain only the N(2) bound isomers for both alkoxy substituted acetylenes.…”
Section: Reaction Of Ruthenium Azido Complexes With Dmd or Dedcontrasting
confidence: 83%
“…Evidence obtained to date indicates that either of the two isomers N(1) and N(2)-bonded are formed simultaneously [7,12,16,26,27] or only the N(2) bound isomer is produced exclusively [7,12,16,17]. In our cases both the N(1) and N(2) bonded isomers are formed depending on the substituents of the triazolato ring.…”
Section: Reaction Of Ruthenium Azido Complexes With Dmd or Dedmentioning
confidence: 65%
“…In analogy, a coordinated azide group in metal complexes can also undergo such cycloaddition reactions [6]. Azido complexes undergo [3+2] cycloaddition reactions with nitriles [7][8][9][10][11][12][13][14][15][16][17][18][19] and isonitriles [7,8,[20][21][22][23] to produce tetrazolato complexes. Similar reactions with alkynes produce triazolates complexes [12,[24][25][26]; alkenes, however, react very slowly and mostly afforded mixture of products [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Part II). With [Pt(N 3 )(CN)(PPh 3 ) 2 ] showing a strict trans ‐configuration and an even more reactive azide ligand one is rid of the problem 49. The interesting thing about trans ‐[Pt(Me)(N 3 )(PPr i 3 ) 2 ], in contrast, is its synthesis from [Pt(N 3 )Me 3 ] 4 and triisopropylphosphine which proceeds by reductive elimination of ethane 62.…”
Section: Heteroleptic Azido Complexesmentioning
confidence: 99%